Different MK-801 administration schedules induce mild to severe learning impairments in an operant conditioning task: role of buspirone and risperidone in ameliorating these cognitive deficits - Rapanelli, Maximiliano (2013)
Blockade of N-methyl-d-aspartate receptor (NMDA) by the noncompetitive NMDA receptor (NMDAR) antagonist MK-801 produces behavioral abnormalities and alterations in prefrontal cortex (PFC) functioning. Due to the critical role of the PFC in operant conditioning task learning, we evaluated the effects of acute, repeated postnatal injections of MK-801 (0.1 mg/kg) on learning performance. We injected Long-Evans rats i.p. with MK-801 (0.1 mg/kg) using three different administration schedules: injection 40 min before beginning the task (during) (n = 12); injection twice daily for six consecutive days prior to beginning the experimental procedures (prior) (n = 12); or twice daily subcutaneous injections from postnatal day 7 to 11 (postnatal) (n = 12). Next, we orally administered risperidone (serotonin receptor 2A and dopamine receptor 2 antagonist, 1 mg/kg) or buspirone (serotonin receptor 1A partial agonist, 10 mg/kg) to animals treated with the MK-801 schedule described above. The postnatal and prior administration schedules produced severe learning deficits, whereas injection of MK-801 just before training sessions had only mild effects on acquisition of an operant conditioning. Risperidone was able to reverse the detrimental effect of MK-801 in the animals that were treated with MK-801 during and prior training sessions. In contrast, buspirone was only effective at mitigating the cognitive deficits induced by MK-801 when administered during the training procedures. The data demonstrates that NMDA antagonism disrupts basic mechanisms of learning in a simple PFC-mediated operant conditioning task, and that buspirone and risperidone failed to attenuate the learning deficits when NMDA neurotransmission was blocked in the early stages of the postnatal period.